Assessing the Population Parameters of Karumballichirus karumba (Poore and Griffin, 1979) from Intertidal Zone of Madura Strait - Jailani, Abdul Qadir; Saputra , Suradi Wijaya; Suryanti; Sabdaningsih , Aninditia (Faculty of Fisheries and Marine Universitas Airlangga, 2025)
Graphical Abstract Highlight Research The Linf CL value in male karumba was 44.21 mm and female was 42.8 mm, with negative allometric growth. The theoretical maximum lifespan (Tmax) of individual karumba, estimated using the VBGF, was 4 to 6 years. The growth coefficient (K) K. karumba is considered quite slow between 0.5-0.9 per year. The exploitation value of karumba is considered vulnerable at this time so that there is a need for management in terms of capture. The results show that recruitment occurs almost every month. Estimated peak recruitment of karumba is around November and January. Abstract This study provides the first information on the population parameters of Karumballichirus karumba. A total of 902 K. karumba samples were collected, consisted of 412 males and 490 females. The von Bertalanffy parameters were estimated to have asymptotic length L∞ (mm): male = 44.21, female = 42.8, and pooled = 44, negative allometric condition factor, growth rate K (/years): male = 0.58, female = 0.67, and pooled = 0.9. Growth performance index (ϕ') : male = 3.05, female = 3.08, and pooled = 3.24. The natural mortality rate M (/years): male =0.7, female = 0.8, and pooled = 1, and shrimp mortality rate F (/years): male = 1.57, female = 2.89, and pooled = 3.12. The current exploitation rate is slightly higher than optimal exploitation rate = 0.5, indicating that there is a need to regulate fishing so that it is sustainable. The size of the first time caught is still below (1/2 Linf); thus, the reproductive opportunities of K. karumba are guaranteed, and in terms of utilization, fall into the category of sustainable fishing. The estimated life span of K. karumba is 4 to 6 years. Reproduction occurs continuously every month, indicated by the discovery of ovigerous females. The highest recruitment occurs in January and November. YPR (yield-per-recruitment) shows that the value of Fcur = 3.12 years⁻¹ in the estimated population is lower than Fmax = 5 years⁻¹ and above F05 = 1.99 years⁻¹ and F01 = 1.8 years⁻¹.